Non-aqueous electrolyte and lithium ion battery
Patent Information
- Application Number
- CN202310888327.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-07-19
AI Technical Summary
[0003]三元正极材料的容量主要来自Ni2+/Ni4+氧化还原,所以镍含量越高,材料的容量也越大,但是Ni含量升高后,三元正极材料会带来一系列棘手的技术问题
[0020] To achieve the above objectives, the present invention also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, and the aforementioned non-aqueous electrolyte, wherein the positive electrode is LiNi. x Co y Mn( 1-x-y M z O2, where 0.6≤x<0.9, x+y≤1, M is at least one of Al, Mg, Zr, Ti, and 0≤z<0.08.
Smart Images

Figure CN117096437B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, and particularly relates to a non-aqueous electrolyte and a lithium-ion battery. Background Technology
[0002] Lithium-ion batteries are among the most common batteries on the market today. The main cathode materials include lithium spinel manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), and ternary cathode materials (LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2 and LiNi 0.8 Co 0.1 Mn 0.1 Among them, ternary cathode materials have advantages such as high energy density, high capacity, and long lifespan, and are widely used in mobile phones, portable computers, electric vehicles, and aerospace.
[0003] The capacity of ternary cathode materials mainly comes from Ni. 2+ / Ni 4+ Redox reactions occur, so the higher the nickel content, the greater the capacity of the material. However, increasing the Ni content brings a series of challenging technical problems to ternary cathode materials. For example, LiNi... 0.8 Co 0.1 Mn 0.1 O2 cathode materials suffer from cation mixing issues; that is, due to the high nickel content, the outer electron configuration during sintering is t. 2g 6 e g 2 Ni 2+ It is easy to combine with the outer electron configuration of t 2g 6 e g 1 Ni 3+ Coexistence occurs, and Ni 2+ radius With Li + radius Very close, causing Ni 2+ It may occupy Li + At position 3b in space, Li + It may occupy Ni 2+ At position 3a, lithium-nickel ion mixing occurs, especially when delithiation occurs at the positive electrode, as Li... +Ni continuously leaves the cathode material. 2+ It will gradually migrate to Li + The vacancies in the cathode material lead to the formation of the NiO phase, making the structure unstable and potentially causing collapse and damage. This results in significant resistance during subsequent lithium intercalation. Furthermore, when the cathode material structure is damaged, the dissolved Ni... 2+ Co 3+ Mn 4+ It will catalyze the continuous decomposition of the electrolyte and the continuous consumption of additives, resulting in poor high-temperature storage of the battery and serious gas generation during circulation.
[0004] Therefore, there is an urgent need to develop a non-aqueous electrolyte that matches high-nickel ternary cathode materials in order to address the shortcomings of existing technologies. Summary of the Invention
[0005] The purpose of this invention is to provide a non-aqueous electrolyte that can significantly improve the room temperature cycle performance, high temperature cycle performance, high temperature storage performance and low temperature discharge performance of lithium-ion batteries.
[0006] Another object of the present invention is to provide a lithium-ion battery that has good room temperature cycle performance, high temperature cycle performance, high temperature storage performance and low temperature discharge performance.
[0007] To achieve the above objectives, the present invention provides a non-aqueous electrolyte comprising a non-aqueous organic solvent, a lithium salt, and an additive, wherein the additive comprises compound A as shown in Formula 1.
[0008]
[0009] R1 is selected from fluorine, chlorine or p-tolyl, and R2, R3, R4, R5 and R6 are each independently selected from hydrogen atom, cyano, nitro, halogen atom, trifluoromethyl, amino, hydroxyl, carboxyl, C1-C3 alkyl, tert-butyl, benzyl, sulfonyl fluoride, C1-C4 alkoxy, C2-C4 alkenyl, C2-C4 alkynyl or C1-C4 acyl.
[0010] Compared with existing technologies, the additive of this invention is a zwitterionic compound containing a sulfonylimide group and a pyridine ring. The negative charge is mainly concentrated on the nitrogen atom bonded to the sulfur atom, while the positive charge is concentrated on the nitrogen atom on the pyridine ring. The sulfonylimide group and the pyridine ring are connected by a carbonyl group, which allows the additive to interact with the lithium salt in the electrolyte, accelerating the dissociation of the lithium salt from the anion ions, thereby improving the ionic conductivity of the electrolyte. Furthermore, due to the instability of the SN bond in the additive structure, it can generate stable S-Li bonds in situ during the formation of the SEI film, increasing the stability of the SEI film. Additionally, the two nitrogen atoms in the additive structure interact with the Li in the cathode material.+ Ni 2+ Co 3+ Mn 4+ It exhibits a certain degree of complexation, making the structure of the cathode material more stable. Therefore, the additive of this invention can significantly improve the room temperature cycle performance, high temperature cycle performance, high temperature storage performance, and low temperature discharge performance of lithium-ion batteries.
[0011] Preferably, R2, R3, R4, R5, and R6 of the present invention are each independently selected from hydrogen atom, cyano group, fluorine atom, trifluoromethyl group, methyl group, sulfonyl fluoride group, vinyl group, ethynyl group, or formyl group.
[0012] Preferably, compound A of the present invention is selected from at least one of compounds 1 to 11:
[0013]
[0014] Preferably, the additive of the present invention accounts for 0.1% to 2% of the total mass of the non-aqueous electrolyte. Specifically, the additive of the present invention may account for, but is not limited to, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, or 2% of the total mass of the non-aqueous electrolyte.
[0015] Preferably, the lithium salt of the present invention is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalate borate (C2BF2LiO4), lithium bis(oxalate borate) (C4BLiO8), lithium difluorophosphate (LiPO2F2), and lithium difluorobis(oxalate phosphate) (LiDFBP). Specifically, the lithium salt of the present invention accounts for 5-25% of the total mass of the non-aqueous electrolyte, and may be, but is not limited to, 5%, 7.5%, 8%, 10%, 13%, 15.6%, 16%, 17%, 19%, 21%, 23%, 24%, and 25%. Preferably, the lithium salt of the present invention accounts for 12.5% of the total mass of the non-aqueous electrolyte.
[0016] Preferably, the lithium salt of the present invention is lithium hexafluorophosphate. Compared with other lithium salts, the additive of the present invention has the strongest interaction with lithium hexafluorophosphate, and the additive can significantly accelerate the dissociation of lithium ions and hexafluorophosphate ions, thereby improving the ionic conductivity of the electrolyte.
[0017] Preferably, the non-aqueous organic solvent of the present invention is at least one selected from ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), propylene carbonate (PC), butyl acetate (n-Ba), γ-butyrolactone (γ-Bt), propyl propionate (PP), ethyl propionate (EP), and ethyl butyrate (Eb). Specifically, the non-aqueous organic solvent of the present invention is a mixture of ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate. Preferably, the non-aqueous organic solvent of the present invention is composed of ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate in a mass ratio of 1:1:1.
[0018] Preferably, the non-aqueous electrolyte of the present invention further includes a film-forming aid selected from at least one of vinylene carbonate (VC), vinylene carbonate (VEC), fluoroethylene carbonate (FEC), vinyl sulfite (ES), 1,3-propanesulfonate lactone (PS), and vinyl sulfate (DTD). Specifically, the film-forming aid of the present invention accounts for 0.1% to 6% of the total mass of the non-aqueous electrolyte. More specifically, the mass percentage of the film-forming aid of the present invention in the total mass of the non-aqueous electrolyte may be, but is not limited to, 0.1%, 0.8%, 1.2%, 1.5%, 2%, 2.5%, 3%, 3.6%, 4%, 4.2%, 4.5%, 4.8%, 5.2%, 5.5%, 5.8%, or 6%.
[0019] Preferably, the film-forming aid of the present invention is a mixture of 1,3-propanesulfonate lactone and fluoroethylene carbonate. More preferably, the film-forming aid of the present invention is composed of 1,3-propanesulfonate lactone and fluoroethylene carbonate in a mass ratio of 1:5.
[0020] To achieve the above objectives, the present invention also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, and the aforementioned non-aqueous electrolyte, wherein the positive electrode is LiNi. x Co y Mn( 1-x-y M z O2, where 0.6≤x<0.9, x+y≤1, M is at least one of Al, Mg, Zr, Ti, and 0≤z<0.08.
[0021] Compared with the prior art, the lithium-ion battery of the present invention includes an additive with a structure of Formula 1, which is an amphoteric compound. This additive interacts with lithium salt in the electrolyte, accelerating the dissociation of lithium salt and acid radical ions, thereby improving the ionic conductivity of the electrolyte. Moreover, due to the instability of the SN bond in the additive structure, it can generate stable S-Li bonds in situ during the formation of the SEI film, increasing the stability of the SEI film. In addition, the two nitrogen atoms in the additive structure interact with the Li in the cathode material. + Ni 2+ Co 3+Mn 4+ The complexation effect makes the structure of the cathode material more stable, thus the lithium-ion battery of the present invention has good room temperature cycle performance, high temperature cycle performance, high temperature storage performance and low temperature discharge performance.
[0022] Preferably, in this invention, x = 0.8, y = 0.1, M is Zr, and z = 0.03.
[0023] Preferably, the negative electrode of the present invention is made of carbon negative electrode material, silicon negative electrode material, or silicon-carbon negative electrode material. Preferably, the negative electrode is made of silicon-carbon negative electrode material, and the mass ratio of silicon to carbon is 1:9. Detailed Implementation
[0024] To further illustrate the purpose, technical solution, and beneficial effects of this invention, the invention will be further described below in conjunction with specific embodiments. It should be noted that, unless specific conditions are specified in the embodiments and comparative examples, conventional conditions or conditions recommended by the manufacturer can be followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0025] Specifically, compounds 1 to 11 of the present invention can be prepared by the following synthetic route:
[0026]
[0027]
[0028] Example 1
[0029] Preparation of non-aqueous electrolytes:
[0030] In a nitrogen-filled glove box (water content ≤1ppm, oxygen content ≤1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were dehydrated using 4A molecular sieve activated with 5% solution mass to ensure the water content of the solution was ≤1ppm. Then, EC, EMC, and DEC were mixed evenly in a mass ratio of 1:1:1 to obtain 81g of solution A. 0.5g of compound 1, 1g of vinylene carbonate (VC), and 5g of fluoroethylene carbonate (FEC) were then added to solution A. Finally, 12.5g of lithium hexafluorophosphate was slowly added and stirred until completely dissolved to form a non-aqueous electrolyte.
[0031] Preparation of the positive electrode:
[0032] LiNi 0.8 Co 0.1 Mn 0.1 Zr 0.03O2 material, PVDF adhesive and Super P conductive agent are mixed evenly in a mass ratio of 97:1:2 to form a slurry. The slurry is then coated on both sides of aluminum foil, and after drying and rolling, the positive electrode is obtained.
[0033] Preparation of the negative electrode:
[0034] The silicon-carbon anode (Si:C = 1:9), conductive agent SuperP, thickener CMC, and binder SBR (styrene-butadiene rubber emulsion) are mixed evenly in a mass ratio of 95:2:1:2 to form a slurry. The slurry is then coated on both sides of a copper foil, and after drying and rolling, the anode is obtained.
[0035] The fabrication of lithium-ion batteries:
[0036] The positive electrode, separator, and negative electrode are stacked to form a square cell, which is then packaged in polymer. A non-aqueous electrolyte is injected into the cell in a glove box, and then a lithium-ion battery with a capacity of 1000mAh is produced through processes such as formation and capacity testing.
[0037] The electrolyte composition of Examples 1-14 and Comparative Examples 1-2 is shown in Table 1. The preparation of non-aqueous electrolyte, positive and negative electrodes, and lithium-ion batteries in Examples 2-14 are exactly the same as those in Comparative Examples 1-2.
[0038] Table 1 Electrolyte Composition
[0039]
[0040] The lithium-ion batteries prepared in Examples 1-14 and Comparative Examples 1-2 were subjected to room temperature cycling tests, high temperature cycling tests, high temperature storage tests, and low temperature discharge performance tests under the following test conditions. The test results are shown in Table 2.
[0041] Room temperature cycling test:
[0042] Under normal temperature (25℃) conditions, the lithium-ion battery is subjected to one 1.0C / 1.0C charge and discharge cycle (battery discharge capacity is C0), with an upper limit voltage of 4.4V, and then subjected to 500 cycles of 1.0C / 1.0C charge and discharge at normal temperature conditions (battery discharge capacity is C1).
[0043] Capacity retention rate = (C1 / C0) * 100%.
[0044] High-temperature cycling test:
[0045] Under high temperature (45℃) conditions, the lithium-ion battery is subjected to one 1.0C / 1.0C charge and discharge cycle (battery discharge capacity is C0), with an upper limit voltage of 4.4V, and then subjected to 300 cycles of 1.0C / 1.0C charge and discharge at room temperature (battery discharge capacity is C1).
[0046] Capacity retention rate = (C1 / C0) * 100%.
[0047] High-temperature storage test:
[0048] Under normal temperature (25℃) conditions, the lithium-ion battery was subjected to one 0.3C / 0.3C charge and discharge cycle (the battery discharge capacity was recorded as C0), with an upper limit voltage of 4.4V. The battery was then stored in a 60℃ oven for 15 days, then removed and brought to room temperature. The battery was then placed in a 25℃ environment and discharged at 0.3C, with the discharge capacity recorded as C1. The lithium-ion battery was then subjected to one 0.3C / 0.3C charge and discharge cycle (the battery discharge capacity was recorded as C2).
[0049] Capacity retention rate = (C1 / C0) * 100%.
[0050] Capacity recovery rate = (C2 / C0) * 100%.
[0051] Low-temperature discharge test:
[0052] At room temperature (25℃), the lithium-ion battery was charged and discharged once at 0.3C / 0.3C (the battery discharge capacity was recorded as C0), with an upper limit voltage of 4.4V; the battery was placed in an environment of -20℃ for 4 hours, and then discharged at 0.3C, with the discharge capacity recorded as C1 and the cutoff voltage of 3.0V.
[0053] Capacity retention rate = (C1 / C0) * 100%.
[0054] Table 2 Performance Test Results
[0055]
[0056]
[0057] Comparing Examples 1-13 with Comparative Example 1, it can be seen that the lithium-ion battery of the present invention has relatively good room temperature cycle performance, high temperature cycle performance, low temperature discharge performance, and high temperature storage performance. This is because the additive of the present invention is an amphoteric compound containing a sulfonylimide group and a pyridine ring. The negative charge is mainly concentrated on the nitrogen atom connected to the sulfur atom, while the positive charge is concentrated on the nitrogen atom on the pyridine ring. The sulfonylimide group and the pyridine ring are connected by a carbonyl group, which allows the additive to interact with the lithium salt in the electrolyte, accelerating the dissociation of the lithium salt from the anion ions, thereby improving the ionic conductivity of the electrolyte. Moreover, due to the instability of the SN bond in the additive structure, it can generate stable S-Li bonds in situ when forming the SEI film, increasing the stability of the SEI film. In addition, the two nitrogen atoms in the additive structure affect the Li in the cathode material. + Ni 2+ Co 3+ Mn 4+ It exhibits a certain degree of complexation, making the structure of the cathode material more stable. Therefore, the non-aqueous electrolyte of this invention can significantly improve the room temperature cycle performance, high temperature cycle performance, high temperature storage performance, and low temperature discharge performance of lithium-ion batteries.
[0058] Comparing Examples 1 to 11, it can be seen that adjusting the substituents with different functions on the pyridine ring will have different effects on the various performance characteristics of the lithium-ion battery. More specifically, the lithium-ion battery in Example 4 has the best performance characteristics. This indicates that introducing five fluorine atoms on the pyridine ring can maximize the wettability of the electrolyte to the cathode material and form a SEI film with more LiF components during the battery formation stage, making the SEI film structure more stable and stronger, thereby maximizing the improvement of the lithium-ion battery's room temperature cycling, high temperature cycling, low temperature discharge, and high temperature storage performance.
[0059] Comparing Examples 1, 6, and 7, it can be seen that introducing unsaturated carbon-carbon double and triple bonds onto the pyridine ring can significantly improve the high and low temperature performance of lithium-ion batteries. This is because the introduced unsaturated double or triple bonds polymerize in situ on the SEI film to form a protective film, making the structure of the SEI film less susceptible to damage during continuous charging and discharging. Furthermore, the polymerized chain ends contain exposed nitrogen atoms. + and N - Atoms can also accelerate Li + Transport within the SEI film results in a higher low-temperature capacity retention rate for lithium-ion batteries.
[0060] Comparing Examples 1 and 9, it can be seen that introducing a fluorosulfonyl group onto the pyridine ring can significantly improve the high and low temperature performance of lithium-ion batteries. This is because the introduced fluorosulfonyl group is a strong electron-withdrawing group that can further disperse the charge on the pyridine ring, making the structure of the compound more stable. Furthermore, during the charge-discharge cycle of the battery, the homolytic cleavage of the S-C bonds generates fluorosulfonyl radicals. These highly reactive radicals will extract oxygen atoms from the electrolyte solvent to form lithium fluorosulfonate. Lithium fluorosulfonate has a simple molecular structure, high stability, and high conductivity, thereby improving the high and low temperature performance of lithium-ion batteries.
[0061] Comparing Example 1 and Example 13, it can be seen that when Compound 1 is used in combination with PS, the high and low temperature performance of the battery is significantly improved. This may be because Compound 1 and PS have similar mechanisms of action, and Compound 1 is preferentially reduced at the negative electrode, forming a dense passivation film at the negative electrode, which improves the high and low temperature performance of the battery.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A non-aqueous electrolyte, comprising a non-aqueous organic solvent, a lithium salt, and an additive, characterized in that, The additive includes compound A as shown in Formula 1. R1 is selected from fluorine, chlorine or p-tolyl, and R2, R3, R4, R5 and R6 are each independently selected from hydrogen atom, cyano, nitro, halogen atom, trifluoromethyl, amino, hydroxyl, carboxyl, C1-C3 alkyl, tert-butyl, benzyl, sulfonyl fluoride, C1-C4 alkoxy, C2-C4 alkenyl, C2-C4 alkynyl or C1-C4 acyl.
2. The non-aqueous electrolyte as described in claim 1, characterized in that, R2, R3, R4, R5, and R6 are each independently selected from hydrogen, cyano, fluorine, trifluoromethyl, methyl, sulfonyl fluoride, vinyl, ethynyl, or formyl.
3. The non-aqueous electrolyte as described in claim 1, characterized in that, Compound A is selected from at least one of compounds 1 to 11:
4. The non-aqueous electrolyte as described in claim 1, characterized in that, The additive accounts for 0.1% to 2% of the total mass of the non-aqueous electrolyte.
5. The non-aqueous electrolyte as described in claim 1, characterized in that, The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate, lithium bis(oxalate borate), lithium difluorophosphate, and lithium difluorobis(oxalate) phosphate.
6. The non-aqueous electrolyte as described in claim 1, characterized in that, The lithium salt is lithium hexafluorophosphate.
7. The non-aqueous electrolyte as described in claim 1, characterized in that, The non-aqueous organic solvent is a mixture of ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate.
8. The non-aqueous electrolyte as described in claim 1, characterized in that, It also includes a film-forming aid selected from at least one of vinylene carbonate, vinylene carbonate, fluoroethylene carbonate, vinyl sulfite, 1,3-propanesulfonate lactone, and vinyl sulfate.
9. The non-aqueous electrolyte as described in claim 8, characterized in that, The film-forming aid is a mixture of 1,3-propanesulfonic acid lactone and fluoroethylene carbonate.
10. A lithium-ion battery, comprising a positive electrode and a negative electrode, characterized in that, It also includes the non-aqueous electrolyte as described in any one of claims 1 to 9, wherein the positive electrode is LiNi x Co y Mn( 1-x-y M z O2, where 0.6≤x<0.9, x+y≤1, M is at least one of Al, Mg, Zr, Ti, and 0≤z<0.08.
Citation Information
Patent Citations
Zwitter-ion-containing high-conductivity electrolyte, preparation method and battery prepared from zwitter-ion-containing high-conductivity electrolyte
CN115189019A
Non-aqueous electrolyte comprising additives for non-aqueous electrolyte, and lithium secondary battery comprising the same
KR1020230057884A